Mengintegrasikan Kearifan Lokal ke dalam Pendidikan Fisika untuk Menumbuhkan Keterampilan Abad ke-21: Tinjauan Konseptual Tematik - Indah Yuliani; Fazia Putri Zahrel; Milya Sari; Hurriyah; Nurhasnah (Jurnal Pendidikan dan Ilmu Fisika, 2026)
This study aims to analyze the integration of local wisdom in physics learning and its contribution to the development of 21st-century skills through a thematic conceptual review approach. The study employed a systematic literature review method by analyzing national and international scientific articles published between 2020 and 2025. The analysis process was conducted through stages of identification, selection, categorization, and thematic synthesis of 20 articles relevant to local wisdom-based physics learning. The findings indicate that the integration of local wisdom enhances students’ understanding of physics concepts, scientific literacy, critical thinking skills, creativity, and learning motivation through contextual and meaningful learning processes. In addition, local wisdom functions as a bridge between scientific concepts and students’ real-life experiences, making learning more relevant to their social and cultural environments. The review also reveals that the effectiveness of local wisdom-based learning is influenced by instructional design, teacher competence, and the availability of contextual teaching materials. However, the implementation in previous studies remains partial and has not been systematically integrated. Therefore, a more comprehensive, applicable, and systematically structured physics learning model based on local wisdom is needed to support the development of 21st-century skills.